Associations of androgens with health care utilization and costs in women—Perspectives of a population-based cohort study. (July 2016) - Haring, Robin; Wallaschofski, Henri; Völzke, Henry; Flessa, Steffen; Keevil, Brian G.; Nauck, Matthias; Baumeister, Sebastian E.
Highlights: This is the first large-scale population-based epidemiological-econometric study to employ sex hormone measurements from liquid chromatography-tandem mass spectrometry. It is the first investigation of potential associations between sex hormones and health care utilization and costs in women. Sex hormone-binding globulin correlated inversely and free testosterone positively with long-term health care costs. Abstract: Objective: Despite associations between total testosterone (TT) concentrations and increased cardiometabolic risk, the impact of serum androgens on health care utilization and costs among women is unknown. Methods: We used data from 1521 women in the population-based cohort Study of Health in Pomerania (SHIP) to investigate the associations of serum TT (measured by liquid chromatography-tandem mass spectrometry), sex hormone-binding globulin (SHBG), and free testosterone (free T) with health care utilization and costs at baseline and five-year follow-up (N = 1210), implementing multivariable-adjusted econometric models. Results: Cross-sectional analyses showed no association of TT, SHBG, or free T with hospitalization or total health costs (outpatient as well as inpatient costs). Prospective analyses revealed an inverse association of baseline SHBG with follow-up total health care costs (% change per standard deviation (SD): −26.2%, 95% confidence interval (CI): −42.2%; −8.9%) and inpatient costs (% change per SD: −26.5%%, 95% CI: −45.5%; −2.5%). Baseline free T was positively associated with total health care costs at the five-year follow-up (% change per SD: +37.7%, 95% CI: +4.6%; +81.4%). Conclusions: In this first cost analysis among women from the general population, we observed no association of androgen serum concentration with health care utilization and costs. However, baseline SHBG appeared to be inversely correlated and free T positively correlated with long-term health care costs.